2014
DOI: 10.1002/j.1532-2149.2013.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Norisoboldine attenuates inflammatory pain via the adenosine A1 receptor

Abstract: Our data demonstrate that NOR produces the analgesic effect in inflammatory pain by a mechanism related to the adenosine system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…1 , 3 -D i p r o p y l -8 -cyclopentylxanthine, an A 1 receptor antagonist, abolishes the effect of CBD on the spikes frequency generated by ON cells and OFF cells in the RVM, while blockade of this receptor reverses the beneficial effect of norisoboldine, which attenuates inflammatory pain [258]. To date, there is no evidence demonstrating a direct implication of adenosine A 2 receptor in the therapeutic action of CBD in pain relief.…”
Section: Cbd Receptor Targets In Painmentioning
confidence: 99%
“…1 , 3 -D i p r o p y l -8 -cyclopentylxanthine, an A 1 receptor antagonist, abolishes the effect of CBD on the spikes frequency generated by ON cells and OFF cells in the RVM, while blockade of this receptor reverses the beneficial effect of norisoboldine, which attenuates inflammatory pain [258]. To date, there is no evidence demonstrating a direct implication of adenosine A 2 receptor in the therapeutic action of CBD in pain relief.…”
Section: Cbd Receptor Targets In Painmentioning
confidence: 99%
“…Moreover, recent studies also suggest that the analgesic efficacy of some herbal preparations long utilized in traditional Chinese medicine can be at least in part due to a modulation of the adenosine system. In fact, norisoboldine (the major active alkaloid component isolated from the dry roots of Lindera aggregata often utilized for chest and abdomen pain, indigestion, cold hernia, and frequent urination) was shown to promote analgesia in both the formalin and the writhing tests in rodents through the activation of A 1 receptor subtype [102]. …”
Section: Adenosine Exerts Analgesic Effects Through Its Glial Recementioning
confidence: 99%
“…Linderae radix, the dried root of Lindera aggregata (Sims) Kosterm, is a traditional Chinese folk medicine possessing anti-inflammatory, analgesic, hepatoprotective and neuroprotective effects. Linderane (LDR), a furan sesquiterpenoid (Figure A), is the main bioactive component isolated from Linderae radix. , Previous studies have shown that LDR could suppress hepatic gluconeogenesis and protect pancreatic β cells from streptozotocin (STZ)-induced oxidative damage. , However, the effects of LDR on regulating sensation and emotion in chronic pain are still unclear. Therefore, the effects of LDR on pain and anxiety were evaluated using the complete Freund’s adjuvant (CFA)-induced inflammatory pain mouse model, and the role of LDR in microglia polarization in the ACC region was also explored in this research.…”
Section: Introductionmentioning
confidence: 99%